SULAMAN KARAWO SEBAGAI DAYA TARIK DI DESTINASI PARIWISATA GORONTALO - Srilian Laxmiwaty Dai (Program Studi S1 Pariwisata, Universitas Muhammadiyah Gorontalo, 2018)
This article analysis the development of karawo embroidery as a tourist attraction. The objectives of this article areto figure out the tourists’ perception, to identify the development phase andto formulate the development strategies of karawo embroidery. The result of this article shows that karawoembroidery overall is excellent. However there are some points need to be improved.karawoembroidery development is in the introduction phase, while the development strategies based on SWOT matrix analysis are: 1) SO strategy is a strategy uses the power to takeadvantages of opportunities to design a tourist attraction package and improving the promotion by the electronic media. 2) ST strategy is a strategy uses the power of addressing threats by making a training and some competitions of karawo embroidery. 3) WO strategy is a strategy that minimizes the weaknesses in taking advantage of opportunities by expanding the distribution, educate the marketer, improve the creativity of the craftswoman and the designer, doing the experiment of creating a tool that can help the craftswoman and distributing flyers at the hotels. 4) WT strategy is a strategy that minimize the weaknesses of avoiding the threats by karawo embroidery preservation and improving the kuality of karawo embroidery